Effectiveness of English for Tourism E-Learning during the Covid-19 Pandemic - Ritonga, Abdul Kadir (Journal of Education Technology, 2022)
The current pandemic situation has resulted in a change in learning methods from face to face to online methods, thus demanding of readiness of lecturers and students to be able to solve problems in order to achieve the learning objectives. In making this online-based tourism English learning method effective, the involvement of lecturers in preparing materials, students in receiving materials, and the use of technology is an inseparable unity. Online learning is an alternative learning method that utilizes the virtual world in the learning process. This study aims to analyze the effectiveness of the online-based English for Tourism teaching and learning process for students with a sample of 130 students taking English courses consisting of Room Division Management, Patisserie Management, Food & Beverage Management, and Tourism Destinations study programs. This type of research was experimental research with pre-experimental research design in the form of the one-shot case study. The instrument by distributing questionnaires was carried out online. Hypothesis testing used one sample t-test analysis with the help of SPSS. The results showed that online-based English for Tourism learning was effective. The results of inferential parametric statistical analysis obtained t-count 83,702 > t-table 1.97852, because the value of t-count was greater than α = 0.05 so H0 was rejected and H1 was accepted. So, it could be concluded that the effectiveness of online learning of English for Tourism was effectively.